DEFINITION AND ANALYSIS OF THE RATIO «PRICE / EARNINGS» OF ACQUIRING AND ACQUIRED COMPANIES - O. Zemlyanskiy (Вестник университета, 2019)
There is offered the method of calculation and formula ratio P/E-ratio «price/earnings» of acquiring and acquired companies. This formula allow determining the maximum value of the ratio at which the cost of shares of the combined company for a period of one year, would be equal to the value of the shares of the acquiring company, under certain forecast profit growth of the company after the acquisition. This formula allow will make analysis of possible changes of this period, if ratio «price/earnings» companies is changing.